circRAPGEF5 Contributes to Papillary Thyroid Proliferation and Metastatis by Regulation miR-198/FGFR1 - Weiwei Liu; Ji Zhao; Mingming Jin; Ming Zhou (Elsevier, 2019)
The circular RNA RAPGEF5 (circRAPGEF5) is generated from five exons of the RAPGEF5 gene and abnormal expression in papillary thyroid cancer (PTC). However, whether circRAPGEF5 plays a role in PTC tumorigenesis remains unclear. The aim of the present study was to investigate the role of circRAPGEF5 in PTC. The results showed that circRAPGEF5 was upregulated in PTC tissues and cell lines. circRAPGEF5 knockdown inhibited cell proliferation, migration, and invasion in vitro; and circRAPGEF5 silencing downregulated fibroblast growth factor receptor 1 (FGFR1) expression by "sponging" miR-198, suppressing the aggressive biological behaviors of PTC. Luciferase reporter assays confirmed that circRAPGEF5 interacted with miR-198 and that miR-198 interacted with the 3' UTR of FGFR1 to downregulate its expression. Xenograft experiments confirmed that circRAPGEF5 knockdown suppressed FGFR1-mediated tumor growth by promoting miR-198 expression. circRAPGEF5 acts as a tumor promoter via a novel circRAPGEF5/miR-198/FGFR1 axis, providing a potential biomarker and therapeutic target for the management of PTC. Keywords: circRNA RAPGEF5, papillary thyroid cancer, miR-198, FGFR1, sponging